Scleral and choroidal volume in relation to axial length in infants with retinoblastoma versus adults with malignant melanomas or end-stage glaucoma - Shen, Ling; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2016)
PurposeTo measure scleral and choroidal volume in eyes of Chinese, and to assess associations with age and axial length.MethodsWe histomorphometrically examined globes from infants and adults which had been enucleated due to retinoblastoma, uveal melanoma, or absolute painful glaucoma. Thickness of sclera and choroid were measured, and volumes were calculated.ResultsThe study included 225 globes (mean axial length: 24.6 ± 4.2 mm; range:17.0-35.7 mm; mean age: 30.4 ± 22.6 years; range: 1-83 years). Mean computed scleral volume was 648 ± 136 mm3. Scleral volume in children aged <5 years significantly increased with longer axial length (P = 0.001; correlation coefficient r: 0.42) and older age (P = 0.003; r: 0.39) in univariate analysis. In multivariate analysis within the group of children aged ≤2 years, larger scleral volume increased with longer axial length (P = 0.04; standardized correlation coefficient beta: 0.32; correlation coefficient B: 21.6; 95 % confidence interval (CI): 0.52, 42.7) and showed a statistically non-significant tendency to increase with older age (P = 0.06;b eta: 0.30; B: 56.9; 95% CI: −1.5,115). In individuals aged ≥ 5 years, scleral volume was not significantly associated with axial length (P = 0.75) or age (P = 0.13). Mean choroidal volume as measured and calculated in 95 individuals (age: 16-81 years) was 44.1 ± 14.1 mm3, and was not significantly associated with age (P = 0.47; r: −0.08) or axial length (P = 0.83; r: −0.02).ConclusionsThis study on children eyes with retinoblastoma and adult eyes with malignant melanomas or end-stage glaucoma suggests that primary eye growth up to an age of 2 years is associated with an increase in scleral volume. After the age of 2 years, scleral volume and choroidal volume remain unchanged, leading to scleral and choroidal thinning with longer axial length, in particular at the posterior pole.